Trolls maintained: baiting technological infrastructures of informational justice. Issue 1 (2nd January 2021) - Kerr, Eric; Lee, Clarissa Ai Ling
ABSTRACT: In this paper, we use trolling to illuminate the entangled and complex relationship between online debate, technological infrastructure, and justice. While a great deal of research has investigated the harmful effects of trolling in the form of cyberbullying and online harassment, attention to the infrastructure of trolling can provide new insights into information flows within digital infrastructure, and consequently, bears on questions such as access to, and quality of, information; the status and credibility of knowledge claims and claimants; and about the gatekeepers of knowledge and information. We show how trolling takes advantage of the rapidity of information transmission and reproduction; technical illiteracy; automation; and 'soft' infrastructure such as conventions, protocols, etiquette, and rules governing online communities to affect informational justice using a methodologically symmetrical approach.